Description of Nursing Students’ Anxiety Levels When Entering Clinical Practices in the Private University in Tangerang - Maria Puji Kris Natalia; Marina Sulistyo Puspaningrum; Michael Momuat; Belet Lydia Ingrit; Komilie Situmorang (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Clinical practice is an integral part of nursing education that helps students to use critical thinking in problems solving. Anxiety can happen because students feel incompetent and lack the skills. This research aimed to describe nursing students’ anxiety level when entering clinical practice at the hospital in a private university in Tangerang. This study used a descriptive research method with total sampling 331 students. Zung Self-rating Anxiety Scale (ZSAS) questionnaire was used as an instrument. The results showed that students with mild anxiety levels were 286 people (86,4%), moderate anxiety were 39 students (11,8%), severe anxiety were five students (1,5%), and panic anxiety was only one student (0,3%). The anxiety level of nursing students is the majority at a mild level of anxiety. Further research needed to decrease anxiety in students when they doing clinical practice in a hospital